Conformational transitions driven by pyridoxal‐5′‐phosphate uptake in the psychrophilic serine hydroxymethyltransferase from Psychromonas ingrahamii. Issue 10 (5th August 2014) - Angelaccio, Sebastiana; Dworkowski, Florian; Di Bello, Angela; Milano, Teresa; Capitani, Guido; Pascarella, Stefano
ABSTRACT Serine hydroxymethyltransferase (SHMT) is a pyridoxal‐5′‐phosphate (PLP)‐dependent enzyme belonging to the fold type I superfamily, which catalyzes in vivo the reversible conversion of l‐serine and tetrahydropteroylglutamate (H4PteGlu) to glycine and 5, 10‐methylenetetrahydropteroylglutamate (5, 10‐CH2‐H4PteGlu). The SHMT from the psychrophilic bacterium Psychromonas ingrahamii (piSHMT) had been recently purified and characterized. This enzyme was shown to display catalytic and stability properties typical of psychrophilic enzymes, namely high catalytic activity at low temperature and thermolability. To gain deeper insights into the structure–function relationship of piSHMT, the three‐dimensional structure of its apo form was determined by X‐ray crystallography. Homology modeling techniques were applied to build a model of the piSHMT holo form. Comparison of the two forms unraveled the conformation modifications that take place when the apo enzyme binds its cofactor. Our results show that the apo form is in an "open" conformation and possesses four (or five, in chain A) disordered loops whose electron density is not visible by X‐ray crystallography. These loops contain residues that interact with the PLP cofactor and three of them are localized in the major domain that, along with the small domain, constitutes the single subunit of the SHMT homodimer. Cofactor binding triggers a rearrangement of the small domain that moves toward the large domain and screens the PLP binding site at the solvent side. Comparison to the mesophilic apo SHMT from Salmonella typhimurium suggests that the backbone conformational changes are wider in psychrophilic SHMT. Proteins 2014; 82:2831–2841. © 2014 Wiley Periodicals, Inc.